Setting national research priorities for difficult-to-treat depression in the UK between 2021-2026 - Chapman, N; Browning, M; Baghurst David; Hotopf, M; Willis, D; Haylock, S; Zakaria, S; Speechley, J; Withey, J; Brooks, E; Chan, F; Pappa, S; et al. (International Society of Global Health, 2022)
Background Difficult-to-treat depression (DTD) presents a substantial health care challenge, with around one-third of people diagnosed with a depressive episode in the UK finding that their symptoms persist following treatment. This study aimed to identify priority research questions (RQs) that could inform the development of new and improved treatments, interventions, and support for people with DTD.